The impact of unfavorable and toxic environmental conditions on autonomic tone modulations while wearing N95 face masks - Valery Erkudov; Andrey Pugovkin; Kenjabek Rozumbetov; Azat Matchanov; Shanika Arachchi; Upaka Rathnayake (Case Studies in Chemical and Environmental Engineering, 2024)
The wearing of respirators has significantly increased over the last years mainly due to the COVID-19 pandemic. The prolonged wearing of respirators may have impacted the Heart Rate Variability (HRV) of the consumer. The scientific community has been attempting to understand the possible influential factors behind it. Unfavorable environmental factors may play a significant role in influencing the HRV for prolonged wearing of the respirators, mainly due to air pollution, and high concentrations of toxic metals and organochlorine compounds in the blood. Hence, this study aims to investigate the influence of unfavorable environmental conditions on the HRV parameters for prolonged wearing of N95 respirators. The study cohort was selected from the young volunteers living in the Aral Sea region, which is infamous for unfavorable environmental conditions due to dust storms with toxic particles, soil salinity, and high usage of pesticides. The study cohort consisted of 1110 male volunteers aged 19–22 and divided into two groups, inhabitants from unfavorable environment (North group) and inhabitants from unaffected environmental conditions (South group). HRV parameters of RMSSD, SDNN, pNN50, HF, LF/HF, SI, SBP, DBP, and SpO2 were measured and statistically compared in two stages, without wearing N95 respirators and while wearing an N95 mask for a 30–40 min period. Our analysis showed a significant increase in RMSSD, SDNN, pNN50 %, and HF parameters while wearing an N95 mask for a 30–40 min period in both groups. SI and LF/HF ratio shows a significant increase while wearing N95 in the «North » group and SI and LF/HF ratio decreased in the «South » group. The prevalence of distribution of subjects having SI more than 150 conv. units while wearing N95 marks in the «North » group were significantly higher compared to the «South » group. Autonomic tone reactivity to the N95 respirators was found in the «North » group in the form of an increase in sympathetic activity. We can conclude that the features of autonomic tone reactivity to wearing N95 respirators were found in the subjects from the environmentally unfavorable regions in the form of measuring the autonomic nervous system imbalance in favor of the increase in SNS activity. This observation is possibly related to the effects of organochlorine pesticides and heavy metals on the human nervous system in the participants living in unfavorable regions of the Aral ecological disaster.